Analisis Efisiensi Produksi Cabai Merah Keriting di Kabupaten Cianjur - Wibisonya, Irawan (LP3M Universitas Putra Bangsa, 2025)
Vegetable commodities are horticultural commodities that have been able to contribute to national development in order to realize community welfare, such as fulfilling community nutrition as a complement to four healthy five perfect foods, this commodity is also very potential and prospective to be cultivated because the cultivation method tends to be easy and simple. In addition to being a superior commodity, vegetable commodities also play a role as a source of community nutrition, a source of foreign exchange, supporting agro-tourism and agro-industry activities. One type of chili that is widely consumed in Indonesia is red chili. Red chili is widely consumed by the community both for household consumption and the food industry. This is important in addition to the potential of red chili which has bright prospects but on the other hand it is necessary to how to stabilize the supply of red chili so that it can still be easily consumed by the community. This study was conducted to measure the level of technical efficiency in curly red chili farming in Cianjur Regency. The data collection method used primary data through interview techniques by taking a sample of 36 farmers in Pacet and Sukanagara Villages. The analysis used was the Stochastic Frontier Cobb Douglass Production Function. The variables used are land area (X1), seeds (X2), labor (X3), NPK fertilizer (X4), and the amount of curly red chili production (Y). To support this research, analysis tools were used in the form of Frontier 4.1 software, Ms Office Excel, and SPSS applications. Based on the results of the study, the majority of chili farmers in Cianjur Regency have been technically efficient. This is indicated by 75% of chili farmers having used production inputs proportionally. On average, chili farmers in Cianjur Regency have achieved a level of technical efficiency with a value of 0.786. There needs to be a standardization of the use of production inputs according to the recommended dose, in addition, the existence of subsidized production input support also needs to be increased in the future.